MPK6 controls H2 O2-induced root elongation by mediating Ca2+ influx across the plasma membrane of root cells in Arabidopsis seedlings - Han, Shuan (The New phytologist, 2015)
© 2014 The Authors. New Phytologist © 2014 New Phytologist Trust.